Radiological Anatomy of the Olfactory Fossa: Is Skull Base Anatomy Really Ever “Safe”? - Hamour, Amr F.; Kus, Lukas; Monteiro, Eric; Scheffler, Patrick; Lee, John; Vescan, Allan (Journal of Neurological Surgery Part B: Skull Base, 2020)
Objective Computed tomography (CT) is a powerful tool for delineating the anatomy of the anterior skull base. The goal of this study is to further characterize the relevant anatomical features of this area, along with other parameters important for endoscopic sinus surgery.Design Retrospective case review.Setting Tertiary care hospital.Participants Thirty patients who had CT scans of the paranasal sinuses.Main Outcome Measures The following features were assessed using image analysis software: olfactory fossa depth, the length and angle of the lateral lamella, fovea ethmoidalis length and shape, ethmoid roof height and slope, and the position and course of the anterior ethmoid artery. Statistical analysis was performed assessing for differences in the above parameters.Results The mean olfactory fossa depth of the anterior and posterior skull base was 3.4  ± 1.1 and 2.4  ± 0.9 mm, respectively (p < 0.05). The mean lateral lamella length was 3.6  ± 0.9 mm, which did not demonstrate significant variability. The angle of the lateral lamella varied significantly by skull base position, measuring 63.1 ± 17.8 degrees anteriorly, and 39.1 ± 17.9 degrees posteriorly (p < 0.05). In scans classified as a Keros type I, 25.3% had lateral lamellae longer than 4 mm. Furthermore, 43.7% had lateral lamellae with angles less than 45 degrees. Moving anteriorly, the posterior skull base sloped downward in 46.7% of patients.Conclusion Thorough preoperative assessment of CT scans is crucial to understanding the inherent variability of skull base anatomy. Even “safe” anatomy can still contain features such as long and acutely angled lateral lamella, which may predispose patients to iatrogenic injury.
Keywords: olfactory fossa; safety; keros; anterior skull base anatomy; sinus surgery